1998
DOI: 10.1021/es970949u
|View full text |Cite
|
Sign up to set email alerts
|

Biological Treatment of TNT-Contaminated Soil. 1. Anaerobic Cometabolic Reduction and Interaction of TNT and Metabolites with Soil Components

Abstract: The explosive 2,4,6-trinitrotoluene (TNT), found as a major contaminant at armament plants from the two world wars, is reduced by a variety of microorganisms when electron donors such as glucose are added. This study shows that the cometabolic reduction of TNT to 2,4,6-triaminotoluene by an undefined anaerobic consortium increased considerably with increasing TNT concentrations and decreased with decreasing concentrations and feeding rates of glucose. The interactions of TNT and its reduction products with mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 29 publications
7
124
2
Order By: Relevance
“…1A) via the sequential addition of three electron pairs to reduce a nitro group to a nitroso group, a hydroxylamino group, and finally an amino group (30). Under strictly anaerobic conditions, all three nitro substituents can be reduced to the amine (5,18). In aerobic systems, partially reduced products accumulate.…”
mentioning
confidence: 99%
“…1A) via the sequential addition of three electron pairs to reduce a nitro group to a nitroso group, a hydroxylamino group, and finally an amino group (30). Under strictly anaerobic conditions, all three nitro substituents can be reduced to the amine (5,18). In aerobic systems, partially reduced products accumulate.…”
mentioning
confidence: 99%
“…pNBS by strain S-313, Table 1) is presumably a function of the K m values of this particular set of transport and desulfonation enzymes, so given the wide range of desulfonative organisms found in nature (Dudley and Frost 1994;Kertesz et al 1994b;King and Quinn 1997;Seitz and Leadbetter 1995) together with enrichment cultures involving complete substrate disappearance, other organisms have more suitable desulfonative enzymes. 8-Amino-1,5-naphthalenedisulfonate 100 3.4 8-Amino-1,5-naphthalene diol 3-Amino-1,5-naphthalenedisulfonate 100 3.0 3-Amino-1,5-naphthalene diol 6-Amino-1,3-naphthalenedisulfonate 0 0 3-Amino-2,7-naphthalenedisulfonate 100 3.3 3-Amino-2,7-naphthalene diol a This compound had similar retention time to the 2,7-diol b The mass spectrum supported the presence of a diol, and the 2,7-naphthalene diol is proposed, because only direct substitution of the sulfono group with the hydroxy group has been observed in these reactions (Dudley and Frost 1994;Kertesz et al 1994b;ZuÈ rrer et al 1987) We presume that the formation of these phenols (Table 1) in soil could lead not only to degradation, but also to binding to clay and to humic fractions (Daun et al 1998;Thorn et al 1996) and to polymerisation reactions (Bollag et al 1992). The latter is presumably indicated both in the rapid disappearance of 4-nitrophenol (Table 1) and the product(s) from ACT.…”
Section: Discussionmentioning
confidence: 93%
“…The latter is presumably indicated both in the rapid disappearance of 4-nitrophenol (Table 1) and the product(s) from ACT. We similarly hypothesise that the stable 2-nitrocresol (Table 1) will be immobilised on clay surfaces, humic materials, possibly via polymerisation after reduction of the nitro group (Bollag et al 1992;Daun et al 1998). All the naphthalene derivatives formed by desulfonation (Table 2) are unstable, so we anticipate that they, too, tend to polymerise or bind or sorb to the soil matrix.…”
Section: Discussionmentioning
confidence: 94%
“…The mutagenic and carcinogenic potential of TNT and its congeners have been reported and there is need to clean up these from the environment 5 . It has been observed that TNT, present in wastewater in concentration of 25-80 mgll, lowered the oxygen consumption of the bacteria by 5-30 per cent, possibly because it inhibited their activity.…”
Section: Effects Of Tnt On the Health Of Personnelmentioning
confidence: 99%